MECHATRONIC DEVICE BASED ON A PARALLEL RECONFIGURABLE MECHANISM FOR ANKLE REHABILITATION (Nexo Revista Científica, 2026)
This work presents the design, construction, and integration of a mechatronic device for ankle rehabilitation. The design is based on a parallel reconfigurable mechanism to be able to execute the three ankle movements with only two actuators. The design and integration of a graphical user interface which allows the device operation is shown too. The rehabilitation robot can execute flexion/extension and adduction/abduction movements in the first operation mode, and eversion/inversion and adduction/abduction movements in the second one. The obtained range of movement are: 46° for flexion, 30° for extension, 36° for both adduction and abduction, 22° for eversion and 17° for inversion. Experimental tests were carried out to verify the mechanism mobility and to demonstrate its viability to be used in therapies of patients who require passive ankle rehabilitation.